A Review on Transforming Patient Pathways: The Impact of Pharmaceutical Software on Drug Manufacturing and Safety Monitoring - Mohd. Wasiullah; Piyush Yadav; Aman Kumar Yadav (Emerging Trends in Personalized Medicines, 2026)
The development, production, and safety monitoring of pharmaceuticals are being revolutionized by incorporating digital technologies. Throughout drug lifecycles, pharmaceutical software which includes cloud-based systems, automation, data analytics, and artificial intelligence (AI) has emerged behind efficiency and innovation. Real-time monitoring, predictive maintenance, and process optimization are made possible in manufacturing by software tools like Digital Twins, Manufacturing Execution Systems (MES), and Quality Management Systems (QMS). These technologies improve batch consistency, lower production costs and schedules, and increase adherence to Good Manufacturing Practice (GMP) standards. Pharmaceutical software is essential for post-market surveillance and pharmacovigilance in addition to manufacturing. Platforms for data integration and analytics driven by AI compile data from patient databases, electronic health records, and clinical trials to increase accuracy of regulatory reporting and identify adverse drug reactions sooner. By guaranteeing quicker access to high-quality medications, promoting individualized treatment plans, and boosting patient confidence in medication safety, these innovations are reshaping patient pathways. The pharmaceutical industry's digital transformation is still accelerating in spite of obstacles like data security, high implementation costs, and interoperability. Pharmaceutical software will continue to be crucial in promoting a safer, more open, and patient-centered healthcare ecosystem as the sector shifts toward increased automation and connectivity
Keywords: Drug manufacturing; Patient pathways; Safety monitoring; digital transformation; pharmaceutical software